Enforcement of Patterns by Constraint-Aware Model Transformations - Lamo, Yngve; Rutle, Adrian; Mantz, Florian (Electronic Communications of the EASST, 2011)
Patterns are descriptions and solutions for recurring problems in software design and implementation. In this paper, some ideas towards a formal approach to the specification of patterns in model-driven engineering (MDE) is presented. The approach is based on the Diagram Predicate Framework which provides a formal approach to (meta)modelling, model transformation and model management in MDE. In particular, patterns are defined as diagrammatic specifications and constraint-aware model transformations are adapted to enforce patterns. Moreover, running examples are used to illustrate the facade design pattern in structural models.